2011
DOI: 10.1186/1756-3305-4-110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two methods of estimating larval habitat productivity in western Kenya highlands

Abstract: BackgroundMalaria vector intervention and control programs require reliable and accurate information about vector abundance and their seasonal distribution. The availability of reliable information on the spatial and temporal productivity of larval vector habitats can improve targeting of larval control interventions and our understanding of local malaria transmission and epidemics. The main objective of this study was to evaluate two methods of estimating larval habitat productivity in the western Kenyan high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 57 publications
6
71
2
Order By: Relevance
“…Other studies has in recent times reported A. arabiensis species proportion of between 29.9 and 33.7% in A. gambiae s.l. larval populations (Ndenga et al, 2011;Kweka et al, 2011). This is despite the few numbers of A. arabiensis adults collected indoors.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies has in recent times reported A. arabiensis species proportion of between 29.9 and 33.7% in A. gambiae s.l. larval populations (Ndenga et al, 2011;Kweka et al, 2011). This is despite the few numbers of A. arabiensis adults collected indoors.…”
Section: Discussionmentioning
confidence: 90%
“…At the beginning of the study, 300 anopheline larval habitats were identified in the three selected villages and characterized based on previous classification (Kweka, Munga, Himeidan, Githeko, & Yan, 2015; Kweka, Zhou, Lee, et al., 2011). In brief, larvae habitats were classified by habitat type (drainage ditches, abandoned gold mines, ponds, fish ponds, roadside canals, rock pools, and swamps) and then identified using unique numbers.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have examined the relationship between habitat characteristics and mosquito larval abundance and distribution in Africa [14-18]. Anopheles arabiensis , the principal malaria vector in Sub-Saharan Africa, prefers shallow clean water and sunlit temporary habitats such as sand pools, brick pits and rain pools [15,16].…”
Section: Introductionmentioning
confidence: 99%